Limb-girdle type muscular dystrophy in a large family with distal myopathy: homozygous manifestation of a dominant gene?. Issue 6 (June 1992) - Udd, B
Abstract : A family study was carried out to clarify the problem of two separate muscle disease phenotypes in a large consanguineous pedigree. These were a severe limb-girdle type muscular dystrophy and a mild late onset distal myopathy. Thirty-two first degree and 14 other relatives of 18 previously examined index patients were available for clinical examination. Twenty-three subjects underwent computed tomography of the lower leg muscles. No new cases of limb-girdle type muscular dystrophy were found. Distal myopathy was diagnosed in 14 subjects, 10 first degree relatives and four other relatives. Segregation analysis showed that the corrected proportion of affected with the severe proximal type was 0.246 and the proportion of affected with the distal myopathy was 0.58. Pedigree analysis is compatible with the possibility that the mild, late onset distal myopathy is caused by a dominant gene and that the limb-girdle type may be expressed in homozygotes.